Karakteristik Bentuk dan Proporsi Gerbang Tradisional Bali Angkul-Angkul pada Permukiman di Desa Gunaksa Klungkung - Anak Agung Ngurah Aritama (Universitas Sebelas Maret Surakarta, 2023)
Gate buildings in traditional Balinese settlements known as angkul-angkul, that classified as sacred building with profane and sacred functions. Angkul-angkul are built with traditional architectural principles that concerning its form and proportion. The study was carried out in settlements area in Desa Gunaksa, Klungkung, as the oldest empire in Bali. This research was conducted using a mixed-method with a descriptive-comparative analysis technique. Found 6 (six) authentic angkul-angkul that are 60-75 years old, that are used as case study to analyze its form and proportion characteristic. Proportion comparison ratio of angkul-angkul’s length: height: width: foot width: body width: roof height: and door opening width is 1 : 2 : 0,5 : 0.35 : 0.28 : 0.40 : 0.26. The study found that proportion comparison of its height and width ratio is 2 : 1, concluded that angkul-angkul in Gunaksa are implement ancient cecandian form with Paushtika proportion based on the Manasara-Silpasastra.